The biopsychosocial board—A conversation tool for broad diagnostic assessment and identification of effective treatment of children with functional somatic disorders. Issue 3 (8th September 2022) - Helgeland, Helene; Gjone, Inger H; Diseth, Trond H
Functional somatic disorders (FSD) result from a complex interplay of biological, psychological, and social factors, the combination of which varies between individuals. Professional and academic communities recommend an integrative, biopsychosocial, and personalized approach in order to achieve early diagnosis, an appropriate understanding of predisposing, triggering, and maintaining factors, and effective treatment. In order to obtain an integrative understanding, constructing a case formulation is suggested to be an important skill for clinicians treating patients with complex health conditions—such as FSD. However, in daily practice, many clinicians are struggling to conceptualize and then implement the biopsychosocial approach into their work with children and their families. This sustains the risk of a fragmented understanding of the child's symptoms and functioning, and consequently fragmentation of health care. As members of a multidisciplinary team of professionals who treat children and adolescents with complex FSD, we here describe and share our experience of a clinical conversational tool—the biopsychosocial board—that we use to promote communication and to achieve an integrative understanding of the patient's symptoms. We highlight the clinician's ability to facilitate and co-construct a biopsychosocial case formulation together with the patient and family because this in the next turn will function as a roadmap to effective and personalized treatment. Used in such a way, we find that our conversation tool has the potential to be an innovative and useful tool for broad diagnostic assessment and identification of effective treatment options tailored to the individual child.